1976
DOI: 10.1021/bi00663a011
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclic electron transport in photosynthesis as measured by the photoinduced turnover of P700 in vivo

Abstract: The light-induced turnover of P700 was measured spectrophotometrically in a wide variety of algae and some photosynthetic mutants. Analysis of the postillumination recovery of P700+ revealed that the apparent first-order rate constant for reduction via the cyclic pathway was much lower that that via the noncyclic pathway. After activation of photosystems 1 and 2 the half-time for reduction of P700+ was 5-20 ms, whereas after activation of primarily photosystem 1 a longer half-time of ca. 150 ms was observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
76
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 34 publications
7
76
0
Order By: Relevance
“…This type of assay gives a measure of the rate of PSII-independent reduction of PSI and is comprised of both cyclic electron transfer around PSI and electron donation to the intersystem electron transfer chain by stromal reductant [8,12]. Fig.…”
Section: 1mentioning
confidence: 99%
“…This type of assay gives a measure of the rate of PSII-independent reduction of PSI and is comprised of both cyclic electron transfer around PSI and electron donation to the intersystem electron transfer chain by stromal reductant [8,12]. Fig.…”
Section: 1mentioning
confidence: 99%
“…Cyclic and linear electron transfers share a common sequence of electron carriers, namely the plastoquinone (PQ) pool, cytochrome b 6 /f complex, and plastocyanin (for review, see Fork and Herbert, 1993;Bendall and Manasse, 1995). This alternative electron flow has been shown to occur in vivo in cyanobacteria (Carpentier et al, 1984), in algae (Maxwell and Biggins, 1976;Ravenel et al, 1994), and in bundle sheath cells of C 4 plants (Herbert et al, 1990;Asada et al, 1993). In cyanobacteria, cyclic electron flow around PS I has been shown to provide extra ATP for different cellular processes, e.g.…”
mentioning
confidence: 94%
“…It was observed that this rate measured in leaves of C 3 plants (e.g. Burrows et al, 1998) was considerably much slower than that measured in the green alga Chlamydomonas reinhardtii (Maxwell and Biggins, 1976;Ravenel et al, 1994) or in cyanobacteria (Mi et al, 1992), suggesting a very slow recycling of electrons around PS I in vivo. The existence of cyclic electron transport in vivo in C 3 plants has also been questioned by photoacoustic measurements in far-red light (Herbert et al, 1990), which allow a direct and quantitative measure of energy storage (ES) by cyclic electron flow around PS I (for review, see Malkin and Canaani, 1994).…”
mentioning
confidence: 96%
See 2 more Smart Citations